Scroll Culture dan Krisis Manajemen Waktu Mahasiswa: Studi Fenomenologis Perspektif al-Qur’an Surah Al-'Asr - Zaid Al Qodhi; Nasrulloh (Al-Kindi, 2026)
The phenomenon of scroll culture has become increasingly prominent in students’ digital lives and has a direct impact on their time-management abilities. This study aims to analyze students’ lived experiences related to uncontrolled social media use and to integrate these findings with the ethical-religious perspective of Surah Al-‘Asr. Employing a qualitative phenomenological approach, data were collected through in-depth interviews with university students who actively use social media. The results reveal recurrent patterns such as automatic scrolling, loss of time awareness, academic procrastination, learning distraction, unproductive use of leisure time, and imbalance between online and offline activities. An integrative analysis using Surah Al-‘Asr shows that scroll culture reflects a form of khusr (loss) as described in the Qur’anic verse, while its resolution may be guided by the four pillars of salvation: faith, righteous action, mutual enjoining of truth, and patience. This study concludes that Surah Al-‘Asr offers a relevant framework for digital self-regulation that can enhance students’ time discipline and productivity in the modern era. The implications highlight the potential of Qur’anic values for informing digital literacy programs, self-regulation training, and contextual time-management strategies for university students.